Peran Guru sebagai Role Model dalam Penanaman Nilai Kejujuran di YPI Qowwiy Azizi - Amini, Aisyah; Haqqie, Fatiah Izzatul; Khaira, Syafiatul (Journal of Sustainable Education, 2025)
This study aims to explore how teachers at YPI Qowwiy Azizi act as role models in teaching students the value of honesty. Honesty is one of the essential foundations of character education for children, and it needs to be nurtured from an early age through consistent example—especially from figures of authority like teachers. Using a qualitative case study approach, the research gathered data through classroom observations, in-depth interviews, and documentation involving both teachers and students. The findings reveal that the way teachers behave—both in and outside the classroom—has a significant influence on how students develop honest attitudes. The study highlights that consistency in the teachers’ actions, clear and open communication, and their willingness to model honesty in everyday situations are key factors in successfully fostering this value. Overall, the presence of teachers as positive role models plays a critical role in shaping students’ moral character, particularly in relation to honesty. These findings suggest that such role modeling can be a powerful and effective strategy in school-based character education programs.